2020
DOI: 10.1098/rspb.2020.0562
|View full text |Cite
|
Sign up to set email alerts
|

Multiple phenotypes conferred by a single insect symbiont are independent

Abstract: Many microbial symbionts have multiple phenotypic consequences for their animal hosts. However, the ways in which different symbiont-mediated phenotypes combine to affect fitness are not well understood. We investigated whether there are correlations between different symbiont-mediated phenotypes. We used the symbiont Spiroplasma , a striking example of a bacterial symbiont conferring diverse phenotypes on insect hosts. We took 11 strains of Spiroplasma infecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Recent findings have implicated Spiroplasma as an anti-parasitoid defender, with resistance to A. ervi being encoded by a modest number of European strains [ 90 , 91 ]. And in our final model for this symbiont ( Table 2 ), we found a positive correlation between its frequency and the proportion of aphids mummifying from A. ervi parasitism (z-value: 3.561; p -value: 0.02884).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have implicated Spiroplasma as an anti-parasitoid defender, with resistance to A. ervi being encoded by a modest number of European strains [ 90 , 91 ]. And in our final model for this symbiont ( Table 2 ), we found a positive correlation between its frequency and the proportion of aphids mummifying from A. ervi parasitism (z-value: 3.561; p -value: 0.02884).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have suggested varying ecological roles for these additional pea aphid symbionts, including defense against the fungal pathogen Pandora neoaphidis ( Regiella , Rickettsia , Rickettsiella , and some strains of Spiroplasma— e.g., [ 86 , 87 ]), thermotolerance ( Serratia and Rickettsia , e.g., [ 74 , 88 , 89 ]), and possible further defense against Aphidius ervi or other parasitoids ( Spiroplasma [ 90 , 91 ]). Fukatsuia symbionts have been shown to impact all three phenotypes in European pea aphids [ 92 , 93 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spiroplasma and Serratia symbiotica did not alter expression of either gene, but two strains of Hamiltonella defensa significantly downregulated PO1 expression but not hemocytin (post-hoc tests, S2 Table and Fig 1D and 1E , right panels). Like Regiella , the specific strain of Spiroplasma (.161) we used was found in previous work to protect against fungal pathogens [ 49 ], but Serratia and Hamiltonella have been shown not to influence fungal resistance [ 36 , 50 , 51 ]. These results therefore suggest that the changes we identify in immune gene expression do not reflect the mechanism by which Regiella confers protection to aphids against fungal pathogens, which is currently unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Pea aphids reproduce by apomictic parthenogenesis under long photoperiod conditions (16h:8h light: dark cycle) allowing us to maintain genetically-identical stocks in the laboratory for extended periods of time. Microsatellite typing was used to verify that the lines used in experiments were correctly assigned to the 'Medicago sativa' biotype [20,21], and to ensure that the lines used were genetically distinct from one another. We screened aphids for the seven known pea aphid facultative symbionts using diagnostic PCR [22], and we then cleared all such symbionts using oral administration of specific antibiotics which do not impact the aphid primary PLOS ONE symbiont, Buchnera aphidicola, as described in [23].…”
Section: Experimental Insectsmentioning
confidence: 99%
“…We used the results of the above experiments to choose two groups of contrasting aphids (each comprising three aphid lines): one group was vulnerable to A. ervi (genotypes C218, C215 and C681) and the other highly resistant (genotypes C308, C207, and C238). We ensured that the lines selected were genetically distinct based on the microsatellite sequencing [20,21] and did not contain pairs of highly-related genotypes within groups. In order to keep conditions as similar as possible between treatments, we used virgin female wasps for this experiment (as wasps are haplodipoid, this means all eggs laid will be male).…”
Section: Exposure To Aphidius Ervi For Transcriptome Sequencingmentioning
confidence: 99%